Cербська баянно-акордеонна школа народної музики: історико-педагогічний аспект - Устименко-Косоріч, Олена (Studies in Comparative Education, 2015)
У статті проаналізовано соціокультурні умови та педагогічні принципи функціонування двох напрямків фахової підготовки баяністів-акордеоністів у Сербії, які суттєво відрізняються в аксіологічному та професійно-технологічному сенсі: рівнем фахової компетентності педагогів, мотивацією навчання особистості, змістом творчо-практичних і педагогічних дій освітніх закладів, визначенням їхнього статусу в контексті науково-освітньої політики країни й суспільної свідомості. Доведено, що сербський національний музично-освітній феномен визначається існуванням академічної музичної освіти та баянно-акордеонної школи народної музики, які в єдності утворюють своєрідний художньо-духовний пласт інструмен-тальної традиції в культурі Сербії. У статті визначено зміст ключових понять роботи, розкрито специфіку діяльності сербських шкіл народної музики та здійснено порівняльний аналіз академічного та народного напрямів підготовки баяністів-акордеоністів у системі музичної освіти Сербії. В статье проанализированы социокультурные условия и педагогические принципы функционирования двух направлений профессиональной подготовки баянистов-аккордеонистов в Сербии, которые существенно отличаются в аксиологическом и профессионально-технологическом смысле: уровнем профессиональной компетентности педагогов, мотивацией обучения личности, содержанием творчески-практических и педагогических действий образовательных учреждений, определением их статуса в контексте научно-образовательной политики страны и общественного сознания. Доказано, что сербский национальный музыкально-образовательный феномен определяется существо-ванием академического музыкального образования и баянно-аккордеонной школы народной музыки, которые в единстве образуют своеобразный художественно-духовной пласт инструментальной традиции в культуре Сербии. В статье определено содержание ключевых понятий работы, раскрыта специфика деятельности сербских школ народной музыки и осуществлен сравнительный анализ академического и народного направлений подготовки баянистов-аккордеонистов в системе музыкального образования Сербии. The article analyzes the socio-cultural conditions and pedagogical principles of two directions of professional training of Bayan-Accordion in Serbia, which significantly differ in axiological and vocational and technological sense: the level of professional competence of teachers, teaching individual motivation, creative and practical content and pedagogical actions, definition of their status in the context of scientific and educational policy and public awareness. It is proved that the Serbian national music and educational phenomenon is determined by the existence of academic musical education and commonplace-school accordion folk music, which form a kind of unity of artistic and spiritual layer of instrumental tradition in the culture of Serbia. The article defines the meaning of key concepts, disclosed the specifics of the Serbian folk music school and makes a comparative analysis of national academic and training areas in Bayan-Accordion music education system in Serbia. National music schools emerged in the 1920s of the twentieth century and are today characterized as commonplace accordion-school folk music. Analysis of references showed that in the terminology database this term is not defined, which gave grounds for its interpretation. Considerring the notion «private school» we understand Serbian bayan-accordion schoolof folk music as a network of private musical and educational institutions of alternative nature aimed at preparing Bayan-Accordion specialists of ethno-cultural destination. It is proved that Serbian accordion schools of folk music operates and develops under the influence of certain cultural trends in the country and are a unique musical and educational phenomenon within the world of music and education. It was found that Serbian national accordion school had a peculiarity – verbal tradition which explained the logic of transferring the musical and educational information from master to a pupil. A school of folk music is seen as creative and performing music base having educational nature and including the Bayan-Accordion educational activities, based on traditional forms of music.